Mathematical population genetics and evolution of bacterial cooperation - Hösel, Volker; Kuttler, Christina 1973-; Müller, Johannes 1965- (World Scientific, 2020)
"Social life of bacteria is in the focus of recent research. Bacteria are simple enough to be accessible by science, but still complex enough to show cooperation, division of labor, bet-hedging, cross-talk and synchronized activities, and a rich variety of social traits. A central question of evolutionary theory is the explanation why this social life did develop, and why these systems are evolutionary stable. This book introduces the reader into the theory of evolution, covering classical models and as well as recent developments. The theory developed is used to represent the up-to-date understanding of social bacteria. This book will be useful for students and lecturers interested in mathematical evolutionary theory, as well as for researchers as a reference"--
Includes bibliographical references and index
Keywords: Populationsgenetik; Mathematisches Modell; Bakterien; Evolution; Population genetics / Mathematical models; Evolution (Biology); Bacteria / Evolution